2016
DOI: 10.1016/j.kjms.2016.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Association of plasminogen activator inhibitor‐1 and vitamin D receptor expression with the risk of keloid disease in a Chinese population

Abstract: Keloid disease (KD) is a benign fibroproliferative scarring condition of unknown etiopathogenesis. Plasminogen activator inhibitor-1 (PAI-1) and vitamin D receptor (VDR) have been shown to play important roles in the progression of tissue fibrosis; therefore, both these genes are potential susceptibility genes for KD. We aimed to determine whether the gene expression levels of PAI-1 and VDR are altered in Chinese KD patients. We measured the expression of PAI and VDR in human peripheral blood lymphocytes in 23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…65 The scar-limiting activity of vitamin D is further supported by the analysis by Gong et al of 236 keloid patients and 219 age-and sex-matched healthy controls that showed keloid patient peripheral blood lymphocytes had significantly lower levels of vitamin D receptor (VDR) mRNA. 66 VDR is a member of the steroid nuclear receptor superfamily that, when bound to the active form of vitamin D, translocates from the cytoplasm to the nucleus and then binds to vitamin D-response elements on the DNA, resulting in the inflammation-and fibrosis-inhibiting activities of vitamin D. 67,68 Similarly, Hahn et al found that excised keloid lesions (n = 24) had overall lower VDR protein levels than skin samples from non-keloid surgical patients (n = 24). Moreover, the epidermis of the keloid samples exhibited significantly less nuclear localization of VDR than the normal samples.…”
Section: Vitamin Dmentioning
confidence: 99%
“…65 The scar-limiting activity of vitamin D is further supported by the analysis by Gong et al of 236 keloid patients and 219 age-and sex-matched healthy controls that showed keloid patient peripheral blood lymphocytes had significantly lower levels of vitamin D receptor (VDR) mRNA. 66 VDR is a member of the steroid nuclear receptor superfamily that, when bound to the active form of vitamin D, translocates from the cytoplasm to the nucleus and then binds to vitamin D-response elements on the DNA, resulting in the inflammation-and fibrosis-inhibiting activities of vitamin D. 67,68 Similarly, Hahn et al found that excised keloid lesions (n = 24) had overall lower VDR protein levels than skin samples from non-keloid surgical patients (n = 24). Moreover, the epidermis of the keloid samples exhibited significantly less nuclear localization of VDR than the normal samples.…”
Section: Vitamin Dmentioning
confidence: 99%
“…The major components of granulation tissue are macrophages, fibroblasts, proteoglycans, hyaluronic acid, collagen, and elastin. Platelet-derived growth factors (PDGF) and TGF-β released by macrophages activate fibroblasts and induce collagen III formation and the creation of an ECM (Gong et al 2017). With the upregulation of vascular endothelial growth factors (VEGF), angiogenesis is also initiated during this phase.…”
Section: Proliferationmentioning
confidence: 99%
“…Individuals with KD are more likely to develop VD deficiency (VDD) (92), hypertension (3), and be dark-skinned (67). Both VDD and hypertension are also more prevalent in dark-skinned populations (67,92).…”
Section: Vitamin D Deficiency In Keloid Disordermentioning
confidence: 99%
“…The genes for plasminogen activator and VDR have been identified as susceptibility genes for KD (92).…”
Section: Vitamin D Deficiency In Keloid Disordermentioning
confidence: 99%